Etika Guru dalam Pengajaran di Lembaga Pendidikan Islam (Studi Kasus di Madrasah Aliyah Negeri 2 Kota Bandung) - Putri, Silviana; Nugraha, Mulyawan Safwandy (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study was conducted with the aim of exploring the role of teacher professional ethics in the teaching process at Madrasah Aliyah Negeri 2 Bandung City. The main focus of this study is to understand how the application of teacher ethics can influence the dynamics of learning and the formation of student character. Teacher ethics include moral responsibility in educating, shaping student behavior, and creating a conducive learning environment. To achieve this goal, a philosophical approach with qualitative methods was used. Data were obtained through in-depth interviews with the principal, Akidah Akhlak teachers, and students to obtain an in-depth perspective on the application of teacher ethics in learning activities. The results of the study revealed that teacher ethics have a significant contribution in creating a positive learning atmosphere. Teachers who consistently carry out moral responsibility are able to build trust, increase student motivation, and create harmonious interactions in the educational environment. The presence of ethical teachers is also a role model for students in developing good attitudes and behaviors. Based on these findings, the study recommends the need for further studies related to the application of teacher ethics at various levels of education. The study is expected to broaden insight and support the development of ethics-based education policies, so as to improve the quality of learning in madrasas and other educational institutions.